2008
DOI: 10.1007/s12205-008-0177-y
|View full text |Cite
|
Sign up to set email alerts
|

Economic effects of microsurfacing on Thermally-Cracked pavements

Abstract: The exclusive effects of microsurfacing on thermal cracks were quantified in terms of IRI. In addition, vehicle operating costs related to the IRI were estimated. For the MnROAD project, using a measurement device with high resolution, pavement surfaces with thermal cracks were profiled before and after microsurfacing. The crack profiles were transferred into longitudinal profiles with no cracks so that the exclusive contribution of original and microsurfaced cracks to roughness could be analyzed. Then, vehicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Microsurfacing asphalt mixtures can be described as a cold mix technology for preventive paving maintenance, which involves the application of a combination of polymermodified asphalt emulsion, well-graded fine aggregate, mineral filler (usual cement), water, and chemical additives (if any) at ambient temperature [5][6][7][8]. Extensive studies conducted by the Texas Transportation Institute (TTI) have confirmed the effectiveness of microsurfacing as a valuable method for preventative maintenance and pavement preservation, leading to a substantial increase in the service life of existing pavements.…”
Section: Introductionmentioning
confidence: 99%
“…Microsurfacing asphalt mixtures can be described as a cold mix technology for preventive paving maintenance, which involves the application of a combination of polymermodified asphalt emulsion, well-graded fine aggregate, mineral filler (usual cement), water, and chemical additives (if any) at ambient temperature [5][6][7][8]. Extensive studies conducted by the Texas Transportation Institute (TTI) have confirmed the effectiveness of microsurfacing as a valuable method for preventative maintenance and pavement preservation, leading to a substantial increase in the service life of existing pavements.…”
Section: Introductionmentioning
confidence: 99%
“…Quick-setting asphalt emulsions are commonly used for treatments like slurry seals and microsurfacing, which involves laying down a mix of aggregate, mineral filler, and diluted asphalt emulsion, to rectify surface defects. 1 Slurry-seal mixes use both polymer-and non-polymer-modified emulsions and are generally used of lower volume roadways, while microsurfacing uses only polymer-modified asphalt emulsions and is often used on higher volume roads. Slurry-seal and microsurfacing mixtures both require emulsions with a quick controlled break, where emulsions need to remain stable when stored and during initial mixing but need to set rapidly once placed in a thin layer on the pavement surface.…”
Section: Introductionmentioning
confidence: 99%
“…Quick-setting asphalt emulsions are commonly used for treatments like slurry seals and microsurfacing, which involves laying down a mix of aggregate, mineral filler, and diluted asphalt emulsion, to rectify surface defects . Slurry-seal mixes use both polymer- and non-polymer-modified emulsions and are generally used of lower volume roadways, while microsurfacing uses only polymer-modified asphalt emulsions and is often used on higher volume roads.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of Santo and Reis (1999), Vale (2003), Vale and Suzuki (2004), Reis (2005), ABEDA (2010), Castro (2011) and Ceratti and Reis (2011) can be highlighted in Brazil. Regarding the international literature, the studies on MS are well established, among which it can be mentioned FHWA (1994), Hick et al (1999), Austroads (2003), Hein et al (2003), Bae and Stoffels (2007), CALTRANS (2009), Broughton et al (2012), Ulhman (2010), NCHRP (2010), ISSA A-143 (2010), Apparoa et al (2013), and Ji et al (2013).…”
Section: Introdutionmentioning
confidence: 99%